Major vault protein suppresses obesity and atherosclerosis through inhibiting IKK–NF-κB signaling mediated inflammation - Jingjing Ben (Nature Portfolio, 2019)
Metabolic diseases are associated with chronic, low-grade inflammation. Here the authors show that major vault protein (MVP) suppresses NF-κB signalling in macrophages via an IRAK1–TRAF6 axis and that loss of MVP in myeloid cells exacerbates the inflammatory response in mice fed a high fat diet.